Sleep apnoea in infants with congenital stridor. Issue 11 (November 1986) - Abreu e Silva, F A; Williams, A; Simpson, H
Abstract : Indices of central apnoea, respiration rate, heart rate, and body movements were comparable in seven infants with congenital stridor (infantile larynx) and matched controls. Obstructive sleep apnoea was only observed in three of seven infants with stridor. Periodic breathing was less common in infants with stridor than in controls.